2019
DOI: 10.3390/molecules24050924
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Species Analysis of Glycosaminoglycan Binding Proteins Reveals Some Animal Models Are “More Equal” than Others

Abstract: Glycosaminoglycan (GAG) mimetics are synthetic or semi-synthetic analogues of heparin or heparan sulfate, which are designed to interact with GAG binding sites on proteins. The preclinical stages of drug development rely on efficacy and toxicity assessment in animals and aim to apply these findings to clinical studies. However, such data may not always reflect the human situation possibly because the GAG binding site on the protein ligand in animals and humans could differ. Possible inter-species differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 76 publications
0
12
0
Order By: Relevance
“…In addition, the GAG chains of danaparoid may be too short and/or mouse might be an inappropriate model. 117 In another set of experiments 137 anti-viral activity, studied as inhibition of rAAV binding to cell-membrane-associated HS, was 80% with therapeutic concentrations of UFH, but equipotent anti-Xa levels of LMWH and danaparoid only achieved <40% and <20% inhibition respectively, while lepirudin had no effect. The results suggest that a high negative charge and possibly longer chain length are essential for blocking or displacing viral interaction with the HS, but they might not necessarily extrapolate to COVID-19 despite the virus exploiting local HS to facilitate cell internalization by attachment to ACE2 receptors.…”
Section: Heparins and Heparinoidsmentioning
confidence: 98%
“…In addition, the GAG chains of danaparoid may be too short and/or mouse might be an inappropriate model. 117 In another set of experiments 137 anti-viral activity, studied as inhibition of rAAV binding to cell-membrane-associated HS, was 80% with therapeutic concentrations of UFH, but equipotent anti-Xa levels of LMWH and danaparoid only achieved <40% and <20% inhibition respectively, while lepirudin had no effect. The results suggest that a high negative charge and possibly longer chain length are essential for blocking or displacing viral interaction with the HS, but they might not necessarily extrapolate to COVID-19 despite the virus exploiting local HS to facilitate cell internalization by attachment to ACE2 receptors.…”
Section: Heparins and Heparinoidsmentioning
confidence: 98%
“…This paradigm views GAGs as the platform enabling differences in the heparin-binding properties of proteins to become functionally relevant. The finding that heparin-binding sites are not fully conserved in homologous proteins of experimental animals and in humans may invalidate some of the preclinical predictions on the activity a GAG will display when administered to humans [161].…”
Section: Summary and Closing Remarksmentioning
confidence: 99%
“…We have examined heparanase in four different animal species to determine whether the critical amino acids for substrate binding in the human enzyme are conserved. This study revealed that the catalytic residues are conserved in the species examined, as were the amino acids involved in hydrogen bonding except for Asn 64 and Thr 97 , and of the residues involved in electrostatic interactions only Lys 159 was not conserved (31). In contrast, the amino acids surrounding the HS binding residues were much less conserved.…”
Section: Introductionmentioning
confidence: 98%
“…These amino acids are Gly 389 , Asn 64 , Tyr 391 , Gly 349 , Gly 350 , Thr 97 , Asn 224 , Gln 270 , and Asp 62 . In contrast, only three amino acids appear to be involved in electrostatic interactions, and these are Lys 159 , Arg 272 , and Arg 303 (25, 31). Earlier reports where homology modeling was used to predict the amino acids interacting with the HS substrate suggested electrostatic interactions with basic residues made a greater contribution (32, 33).…”
Section: Introductionmentioning
confidence: 99%